Performance preserving network downscaling - Govindan, Ramesh; Papadopoulos, Fragkiskos; Psounis, Konstantinos (My University, 2005)
The Internet is a large, complex, heterogeneous system operating at very high speeds and consisting of a large number of users. Researchers use a suite of tools and techniques in order to understand the performance of networks: measurements, simulations, and deployments on small to medium-scale testbeds. This work considers a novel addition to this suite: a class of methods to scale down the topology of the Internet that enables researchers to create and observe a smaller replica, and extrapolate its performance to the expected performance of the larger Internet. The key insight that we leverage in this work is that only the congested links along the path of each flow introduce sizable queueing delays and dependencies among flows. Hence, one might hope that the network properties can be captured by a topology that consists of the congested links only. We show that for a network that is shared by TCP flows it is possible to achieve this kind of performance scaling. We also show that simulating a scaled topology can be up to two orders of magnitude faster than simulating the original topology. © 2005 IEEE.
Keywords: Internet; Traffic control; Network topology; Telecommunication traffic; Delay; IP networks; Testing; Protocols; Performance analysis; Analytical models